Uranium-Thorium analysis from IODP Site 323-U1340 - Kimberly deLong; Terrence Blackburn; Beth Caissie; Jason A Addison; Zuzanna N Stroynowski; Maria Reimi Sipala; Franco Marcantonio; Ana Christina Ravelo (PANGAEA, 2025)
The Bølling-Allerød deglacial event is marked by high diatom productivity and opal deposition throughout the subarctic Pacific. To investigate the cause of this event, we quantified several productivity-related sedimentary parameters that reflect the near-surface biogeochemistry from the Integrated Ocean Drilling Program (IODP) Site 323-U1340 in the Bering Sea. Uranium-Thorium analysis was conducted via isotope dilution analysis in the Marcantonio lab at Texas A&M University. 0.3-0.4 g of sediment were spiked with 229Th and 236U, acid digested, separated and purified via anion exchange chromatography as outlined in Loveley et al. (2017), and measured on an Element XR magnetic sector ICPMS (Fleisher & Anderson, 2003; doi:10.1016/S0967-0645(02)00591-X).